2009
DOI: 10.1002/ejic.200800802
|View full text |Cite
|
Sign up to set email alerts
|

Alkali Metal Tetraselenohypodiphosphonates: Synthesis, NMR Spectroscopy and Crystal Structures

Abstract: The one-pot reaction of alkyl or aryl dichlorophosphanes RPCl 2 with alkali metal selenides M 2 Se and M 2 Se 2 in a 2:2:1 molar ratio provides a simple and general route to alkali metal tetraselenohypodiphosphonates (RP) 2 Se 4 M 2 (M = Li, Na; R = alkyl, aryl). The new compounds were characterized by multinuclear ( 31 P, 77 Se, 1 H, 13 C) NMR spectroscopy and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
(43 reference statements)
1
4
0
Order By: Relevance
“…As expected, the 77 Se satellites in the 31 P NMR spectrum display the eight line pattern for the A part . From this, the 1 J PP coupling constant is directly evaluated and agrees well with the −210 Hz found in tetraselenohypodiphosphonate anions . The 1 J SeP coupling constant (−532 Hz) is in between the values found for two coordinated selenium atoms (P−Se−) and the values observed in phosphorus selenides (R 3 PSe) .…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…As expected, the 77 Se satellites in the 31 P NMR spectrum display the eight line pattern for the A part . From this, the 1 J PP coupling constant is directly evaluated and agrees well with the −210 Hz found in tetraselenohypodiphosphonate anions . The 1 J SeP coupling constant (−532 Hz) is in between the values found for two coordinated selenium atoms (P−Se−) and the values observed in phosphorus selenides (R 3 PSe) .…”
Section: Resultssupporting
confidence: 80%
“…24 From this, the 1 J PP coupling constant is directly evaluated and agrees well with the -210 Hz found in tetraselenohypodiphosphonate anions. 25 The 1 J SeP coupling constant (-532 Hz) is in between the values found for two coordinated selenium atoms (P-Se-) and the values observed in phosphorus selenides (R 3 PdSe). 26 The 2 J SeP coupling constant is 9 Hz.…”
Section: Resultsmentioning
confidence: 56%
“…The “end-on” coordination mode observed in 2 is very different from the “side-on” coordination observed in tetrathiohypodiphosphonate [(C 6 H 11 P(S 2 )) 2 Li 2 (TMEDA) 2 ], in which two five-membered PPSLiS chelate rings are present, both of which include the P–P bond. To our knowledge, the only other example of similar “end-on” coordination as featured in 2 is in the tetraselenohypodiphosphonate complex [(PhP(Se 2 )) 2 Li 2 (TMEDA) 2 ] …”
Section: Resultsmentioning
confidence: 97%
“…The P−P bond is rotated such that the benzyl groups are staggered with respect . 36 Attempts to prepare the trithiophosphonate 1 in higher purity and yield by lowering the reaction temperature to −78 °C in order to minimize the occurrence of the condensation reaction proved unsuccessful, with 31 P NMR showing tetrathiohypodiphosphonate 2 to still be present in the product mixture in appreciable quantity. However, substitution of PhCH 2 PO 3 Et 2 with n PrPO 3 Et 2 did lead to an improvement in yield and purity with the trithiophosphonate 3 obtained in 20% yield as colorless crystals (Scheme 3).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…80 A number of studies have reported the oxidation of P(III) to P(V) by a range of chalcogen sources; reaction of RPCl 2 (R = Me, Et, i Pr, t Bu, Ph, Ad, 2-thiophenyl) with M 2 Se and M 2 Se 2 (2 : 2 : 1) afforded [(RP) 2 Se 4 ]M 2 (M = Li, Na). 81 82 Hydrophosphination of appropriate alkenes followed by oxidation by elemental chalcogen (S, Se) produced extremely bulky secondary phosphine chalocogenides in excellent yield. 83 A new series of arylselenium(II) derivatives of dithiophosphorus ligands ArSeSP(S)R 2 [R = Ph, or OR] have been prepared from Ar 2 Se 2 and [R 2 P(S)S] 2 .…”
Section: àmentioning
confidence: 99%